2017 15th International Conference on Emerging eLearning Technologies and Applications (ICETA) 2017
DOI: 10.1109/iceta.2017.8102483
|View full text |Cite
|
Sign up to set email alerts
|

Speech interface dialog with smart glasses

Abstract: This paper describes design of elderly-user-friendly multi-mode user interface with different modules. Use of eye glasses is common among senior citizens, and it inspired us to implement interface modules on it. Indicator-based Glasses contains the Eye Blinking Detection module integrated with visual cues indicators as system feedback. The multi-mode interface provides five interaction channels by proposing audio input/output modules and Android application on smartphone device. The VoiceXML Dialog Manager imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For medical uses, techniques have been presented for clinical and surgical applications [8], medical emergency situations [9], and disaster medicine [10]. For recognition and interface, techniques have been presented for head gestures [11], face detection [12], eye movements [13], user authentication [14], estimation of respiration rate [15], speech interaction with eye blinking detection [16], context-aware lightning control [17], distance learning [18], and indoor localization [19], drowsiness and fatigue detection to increase road safety [20], countermeasures to phishing attacks [21], gait aid for Parkinson's disease patients [22], contextually-aware learning in physics experiments [23], and guiding for visually impaired users [24]. Some techniques regarding thermals have been presented such as 3D thermal model reconstruction based on image-based modeling using smartphone sensors [25], design of an oven utilizing radiative heat transfer for smart phone panels [26], thermal management systems for civil aircraft engines [27], and thermal properties of glasses [28].…”
Section: Introductionmentioning
confidence: 99%
“…For medical uses, techniques have been presented for clinical and surgical applications [8], medical emergency situations [9], and disaster medicine [10]. For recognition and interface, techniques have been presented for head gestures [11], face detection [12], eye movements [13], user authentication [14], estimation of respiration rate [15], speech interaction with eye blinking detection [16], context-aware lightning control [17], distance learning [18], and indoor localization [19], drowsiness and fatigue detection to increase road safety [20], countermeasures to phishing attacks [21], gait aid for Parkinson's disease patients [22], contextually-aware learning in physics experiments [23], and guiding for visually impaired users [24]. Some techniques regarding thermals have been presented such as 3D thermal model reconstruction based on image-based modeling using smartphone sensors [25], design of an oven utilizing radiative heat transfer for smart phone panels [26], thermal management systems for civil aircraft engines [27], and thermal properties of glasses [28].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the Voice XML Dialog Manager (VoiceON) has been explained by Firouzian et al [13]and suggested for voice facilitated dialogues. The major objective of the proposed system is senior citizens who suffer from mild & moderate dementia.…”
mentioning
confidence: 99%